Human auditory event-related potentials to frequency changes in speech and non-speech sounds. - Maiste, Anita. (University of Ottawa (Canada), 1989)
This thesis presents two approaches investigating how the human auditory system processes the brief frequency changes that occur in speech sounds. Section 1 of the thesis consists of a critical review of the literature on human auditory event-related potentials (ERPs) and speech perception. Section 2 consists of three experiments evaluating ERPs to non-speech frequency changes. The experiments evaluated steady state and transient auditory evoked potentials (EPs) to tones that were sinusoidally modulated in frequency and to tones that alternated between two frequencies with a linear ramp. The tones were presented at modulation rates typical of average syllable production. The steady state responses to sinusoidal FM were small and difficult to record at both the first and second harmonics. Ramp FM evoked larger and more consistent second harmonic steady state responses than the sinusoidal FM. Only the ramp FM stimuli elicited transient EPs and these only at low modulation rates. These responses were larger to upward ramps than to downward ramps. The response to two simultaneously presented ramp FM tones differed from the sum of responses to the individual tones indicating some interaction in the processing of the two stimuli. Since the first study found that steady state responses were not as reliable as ERPs to discrete frequency changes, the second study used speech sounds containing discrete frequency changes. In Section 3 of the thesis computer-modified speech sounds from the /ba/ to /da/ continuum were presented to reading subjects as a train of standard speech sounds interspersed with two types of infrequent deviant speech sounds. One deviant stimulus lay within the same category as the standard and the other lay across the categorical boundary from the standard, but both were acoustically equidistant from the standard in terms of the second formant transition. When the standard stimulus was drawn from the /ba/ end of the continuum, the across-category deviants elicited a clear mismatch negativity (MMN) in the auditory event-related potential whereas the within-category deviants did not. This MMN began at about 60-120 ms after stimulus onset and was present for several hundred ms. These results suggest that categorical processing of speech sounds occurs independently of attention at an early echoic memory stage. When the standard stimulus was drawn from the /da/ end of the continuum, the MMN to across-category deviants was not larger than the MMN to within-category deviants. Grand mean waveforms suggested that both deviant stimuli elicited small MMNs. Although this may indicate processing along an acoustic continuum, the results of the psychophysical tests suggest that the standard stimulus in this condition was too close to the category boundary for the deviants to evoke a consistent categorical mismatch.
Keywords: Health Sciences, Audiology.